Multiple recycled aggregate properties analysed by X-ray microtomography. (30th March 2018) - Thomas, C.; de Brito, J.; Gil, V.; Sainz-Aja, J.A.; Cimentada, A.
Highlights: Multiple recycling properties of recycled aggregate has been analysed. Computerized micro-tomography identifies phases of the recycled aggregate. After 3 recycling the volume of adhered mortar is 80% of the aggregate. Density decreases with recycling cycles and the size of the aggregate. Abstract: This paper presents a novel technique used to analyse the volume of adhered mortar to the recycled aggregate. A computerized microtomograph (μCT) device was used to evaluate the volume of the aggregate, the volume of natural aggregate and the volume of adhered mortar. To this end, a natural aggregate has been characterized, using the μCT, with which a source concrete has been produced. Subsequently, the source concrete has been crushed to obtain a first cycle recycled aggregate. After the characterization of the first-generation of recycled aggregate, a new source concrete has been made with it to be subsequently crushed again obtaining a second-generation recycled aggregates. In the same way a third-generation recycled aggregate has been obtained and has been equally characterized. The results show that the compaction capacity of the aggregate is reduced after successive recycling. It has been possible to quantify how much the closed porosity of the recycled aggregate decreases with the number of times it is recycled. The loss of natural aggregate and increase of the volume of adhered mortar have also been evaluated using this technique.